Hemolytic anemia associated with intravenous immunoglobulin in Kawasaki disease - Eun Jung Cheon; Jun Suk Oh (BMC Pediatrics, 2024)
Abstract Background The administration of high-dose intravenous immunoglobulin (IVIG) is a standard treatment for the management of Kawasaki disease (KD). IVIG is known to be a highly effective and safe treatment. Case presentation We report the development of hemolytic anemia in seven children receiving repeated doses of IVIG. The children were aged 3–44 months and included 4 girls and 3 boys. All children received 10% IVIG and a second course of immunoglobulin because they did not respond to the first course of immunoglobulin. Two received high-dose aspirin (50 mg/kg), and five received low-dose aspirin (5 mg/kg). Two patients required additional methylprednisolone pulse therapy (30 mg/kg) after the second dose of immunoglobulin, and three patients received oral prednisolone therapy for defervescence. Three patients showed coronary artery dilation during hospitalization and normalized within two months. Pretreatment hemoglobin averaged 11.3–14.2 g/dL, and post-hemolytic anemia hemoglobin ranged from 7.4 to 9.6 g/dL, with a difference of 1.7–6.8 g/dL. Reticulocytes were increased to 3.3–13.2%. Peripheral blood smears showed normochromic normocytic anemia, and anisopoikilocytosis. All children were positive for warm-type antibodies with IgG+, C3d- in direct antiglobulin test, and the blood group was A + in five and B + in two. None of the patients received immunomodulatory therapy or red blood cell transfusions. They were followed for a year and all recovered. Conclusion Especially, in non-O blood group KD patients who are refractory to initial IVIG and require a second dose of IVIG or 10% formulation the possibility of immune hemolytic anemia should be carefully considered, and close follow-up should be maintained after therapy.